Annual Financial Statements - Report Of The Independent Auditors (The Southern African Institute of Mining and Metallurgy, 2006)
To the members of The South African Institute of Mining and Metallurgy I have audited the annual financial statements of The South African Institute of Mining and Metallurgy set out on pages 641 to 644 for the year ended 30 June 2006. These annual financial statements are the responsibility of the Institute?s Council members. My responsibility is to express an opinion on these annual financial statements based on my audit. Scope I conducted my audit in accordance with International Standards on Auditing. Those standards require that I plan and perform the audit to obtain reasonable assurance about whether the annual financial statements are free of material misstatement. An audit includes: ?examining, on a test basis, evidence supporting the amounts and disclosures in the annual financial statements, ?assessing the accounting policies used and significant estimates made by management, and ?evaluating the overall financial statement presentation. I believe that my audit provides a reasonable basis for my opinion. Audit opinion In my opinion, the annual financial statements present fairly, in all material respects, the financial position of the Institute at 30 June 2006 and the results of its operations and cash flows for the year then ended in accordance with generally accepted accounting practice appropriate to the Institute. Supplementary information The supplementary schedule does not form part of the annual financial statements and is presented as additional information. I have not audited this schedule and accordingly do not express an opinion on it.